2020
DOI: 10.1038/s41598-020-68926-y
|View full text |Cite
|
Sign up to set email alerts
|

Subliminal determinants of cue-guided choice

Abstract: By anticipating potential rewards, external cues can guide behavior to achieve a goal. Whether the conscious elaboration of these cues is necessary to elicit cue-guided choices is still unknown. the goal of the present study is to test whether the subliminal presentation of a visual cue previously paired with a reward is sufficient to bias responses that can lead to the same or a similar reward. To this aim, three experiments compared the subliminal and supraliminal presentation of reward-associated cues durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
(177 reference statements)
4
16
0
Order By: Relevance
“…sharing the appetitive value, general transfer). These results are in line with and extend the current literature on cue-guided choice, supporting the idea that separate neural substrates underpin these two effects and further highlighting a dissociation between outcome-specific and general transfer (Bray et al, 2008;Garofalo et al, , 2019Garofalo et al, , 2020Garofalo & di Pellegrino, 2015Lewis et al, 2013;Morris et al, 2015;Prévost et al, 2012;Talmi et al, 2008). Moreover, the present results shed new light on the cortical structures involved in cue-guided choice by providing the first evidence for direct involvement of the lateral prefrontal cortex in outcome-specific transfer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…sharing the appetitive value, general transfer). These results are in line with and extend the current literature on cue-guided choice, supporting the idea that separate neural substrates underpin these two effects and further highlighting a dissociation between outcome-specific and general transfer (Bray et al, 2008;Garofalo et al, , 2019Garofalo et al, , 2020Garofalo & di Pellegrino, 2015Lewis et al, 2013;Morris et al, 2015;Prévost et al, 2012;Talmi et al, 2008). Moreover, the present results shed new light on the cortical structures involved in cue-guided choice by providing the first evidence for direct involvement of the lateral prefrontal cortex in outcome-specific transfer.…”
Section: Discussionsupporting
confidence: 91%
“…Based on this evidence, we argue that sensory-specific cue-guided choice is likely to rely on the lateral prefrontal cortex for the active maintenance of a detailed representation of the sensory properties of each choice-reward pairing elicited by the cue which are, in turn, used to direct choice. In line with this, previous studies showed that high-level cognitive abilities, such as working memory (Garofalo et al, 2019), and supraliminal (vs subliminal) presentation of the reward-associated cue (Garofalo et al, 2020) are crucial for the expression of outcome specific, but not general transfer. In contrast, such area may not be as crucial for the general form of cue-guided choices which results from an increase in motivation towards obtaining any reward, and may rather rely on subcortical areas (Corbit & Balleine, 2015;Dolan & Dayan, 2013;Holland, 2004).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Human beings tend to adjust their behaviors according to the rewards they might gain. To date, considerable studies have been carried out on human reward system, indicating that rewards can improve the performance of cognitive functions, such as working memory ( Bijleveld et al, 2011 ; Capa et al, 2013 ), conflict monitoring ( van Gaal and Lamme, 2012 ), bias responses ( Garofalo et al, 2020 ), self-face processing ( Zhan et al, 2017 ), and cognitive inhibition ( Diao et al, 2016 ). Drawing on an incentive force task, Pessiglione et al (2007) inspected the activation of the brain to the unconscious monetary reward cues, which revealed that the motor function could be improved with higher amounts of unconscious monetary reward, as compared to that with lower ones.…”
Section: Introductionmentioning
confidence: 99%